Literacy as placed resource in the context of a rural community member’s everyday lives: The case of Bweyale in Uganda - Openjuru, George Ladaah (Routledge, 2016)
Literacy is a placed resource that is used differently in the different places of everyday life in rural communities. Bweyale is a multilingual rural community in Uganda. In this chapter, I report a study of rural community literacy use in Bweyale to show how literacy used varies from one place to another. Literacy pervades every aspect of rural community life and rural people use literacy in many rich and creative ways. Contexts for literacy use include rural community livelihoods, education, religion, bureaucracy, household and personal life. The ethnographic study reported in this chapter was informed by the theory of literacy as social practice. The findings show that literacy use is influenced by activities which are embedded in the different spaces in which people are involved as they live their everyday lives.
Keywords: Literacy; Rural community; Uganda